Our journey with François Gros - Butler-Browne, Gillian; Mouly, Vincent (Comptes Rendus Biologies, 2023)
Gillian Butler-Browne began working on muscle at the Institut Pasteur in the laboratory of François Gros in 1978. She characterized the expression profile of different myosin isoforms during both human and rodent development. Vincent Mouly joined this laboratory for his PhD in 1982, and defined the different populations of myoblasts appearing during development in birds and then in humans. Together, they demonstrated the impact of the limit in proliferation of the precursor cells on the regenerative capacity of human skeletal muscle, and their group developed models to evaluate the regenerative potential of skeletal muscle in vitro, measuring the telomeric erosion, and identified the involvement of a stress pathway in the proliferative arrest of muscle progenitors. A platform to produce human immortalized muscle cell lines was the successful result of this research, initiated with François Gros and W. E. Wright. The in vivo regenerative potential of human muscle cells was evaluated by injection into muscles of immunodeficient mice. Their group in collaboration with the clinical team of Professor Jean Lacau St-Guily and Professor Sophie Perié completed a successful autologous myoblast transplantation clinical trial for Oculo-pharyngeal muscular dystrophy. This common scientific career was made possible thanks to the precious and always benevolent support of François Gros.